PERKULIAHAN DENGAN MODEL PEMBELAJARAN JIGSAW BERBANTUAN MEDIA PRESENTASI POWERPOINT DISERTAI VISUAL BASIC APPLICATIONS UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS MAHASISWA - Loka Son, Aloisius; Nur Ahzan, Zulkaidah (Universitas Wiralodra, 2017)
The ability of mathematical communication is very important for prospective students of mathematics teachers, in order to be able to communicate their mathematical ideas both orally and in writing to others clearly, precisely and effectively. Therefore, prospective students of mathematics teachers need to be equipped with mathematical communication skills when taking the lecture through a student-centered lecture model and utilizing the ever-evolving information technology and communication, so this research aims to improve student’s mathematical communication skills through Jigsaw learning model assisted by media presentation powerpoint accompanied visual basic applications. This research is a kind of quasi experimental research conducted on a second-year student of Mathematics Education Study Program of University of Timor in 2015/2016 academic year. Data collection techniques that is used are test of mathematical communication skills. While the data analysis technique that is used is the one sample t test, two sample t test, and effect size test. The results showed that student’s mathematical communication skills taught by Jigsaw learning model with powerpoint presentation media along with visual basic applications better than the student’s mathematical communication skills taught by conventional learning model with the size of the effect size in the big category that is 0.92.